2017
DOI: 10.1016/j.ebiom.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

FASN Inhibition and Taxane Treatment Combine to Enhance Anti-tumor Efficacy in Diverse Xenograft Tumor Models through Disruption of Tubulin Palmitoylation and Microtubule Organization and FASN Inhibition-Mediated Effects on Oncogenic Signaling and Gene Expression

Abstract: Palmitate, the enzymatic product of FASN, and palmitate-derived lipids support cell metabolism, membrane architecture, protein localization, and intracellular signaling. Tubulins are among many proteins that are modified post-translationally by acylation with palmitate. We show that FASN inhibition with TVB-3166 or TVB-3664 significantly reduces tubulin palmitoylation and mRNA expression. Disrupted microtubule organization in tumor cells is an additional consequence of FASN inhibition. FASN inhibition combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 51 publications
5
93
0
3
Order By: Relevance
“…FASN plays critical roles in different aspects of the tumor biology involved in cell metabolism but also integrating signaling pathways, contributing to post-translational palmitoylation and impacting membrane structure and function. 40 Cancer cell metabolism is characterized by high levels of glycolysis, glutaminolysis and de novo synthesis of fatty acids, resulting from the activation of cancerpromoting factors including c-Myc and NF-jB and the inactivation of tumor suppressor genes such as p53 and PTEN. All these factors converge at the level of PI3K/AKT and the ERK/MAPK pathways, which promote the generation of the energy required for sustained tumor cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…FASN plays critical roles in different aspects of the tumor biology involved in cell metabolism but also integrating signaling pathways, contributing to post-translational palmitoylation and impacting membrane structure and function. 40 Cancer cell metabolism is characterized by high levels of glycolysis, glutaminolysis and de novo synthesis of fatty acids, resulting from the activation of cancerpromoting factors including c-Myc and NF-jB and the inactivation of tumor suppressor genes such as p53 and PTEN. All these factors converge at the level of PI3K/AKT and the ERK/MAPK pathways, which promote the generation of the energy required for sustained tumor cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inhibition of FASN and palmitate production by orlistat and NanoOrl may affect post-translational modification of tubulin, and thus affect microtubule stability. A recent paper using the FASN inhibitors TVB-3166 and TVB-3664 showed that FASN inhibition reduced tubulin palmitoylation and disrupted microtubule organization in tumor cells (53). The authors showed that FASN inhibition combined with taxane treatment enhances inhibition of in vitro tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic knockdown of ACC induces apoptosis in cancer cell lines (Brusselmans et al, 2005; Chajes et al, 2006), and an allosteric inhibitor of ACC, ND-646, has shown antitumor efficacy in autochthonous mouse lung tumor models (Svensson et al, 2016). Targeting FASN has been found to reduce palmitoylation of tubulin and disrupt microtubule organization, inhibiting tumor cell growth (Heuer et al, 2017). The compound TVB-2640 is the first compound targeting FASN to enter clinical trials (Table 1), and when combined with paclitaxel, can cause partial responses or prolonged stable disease (Brenner et al, 2017).…”
Section: Emerging Metabolic Targetsmentioning
confidence: 99%